Performance analyses of horizontal axis wind turbines using QBlade - Zuhdi, Amirul Hakim; Islam, Mazharul (2017)
Wind turbines are considered as a renewable energy technologies which have the potential to reduce environmental pollutions from conventional energy sources. Currently, many research activities have concentrated on improving and modifying the aerodynamic performances of wind turbine blades through wind tunnel testing and complicated computational investigations (like CFD). In the present research, a freely available wind turbine simulation software called QBlade is used, which is computationally inexpensive for performance and design analyses of wind turbines. In the present research, performance analysis of a smaller-capacity horizontal axis wind turbine (HAWT) with QBlade have been conducted. After validating the obtained results with existing experimental results, comparative performance study have been conducted using three airfoils.